2020
DOI: 10.1073/pnas.2012358117
|View full text |Cite
|
Sign up to set email alerts
|

Reduced development of COVID-19 in children reveals molecular checkpoints gating pathogenesis illuminating potential therapeutics

Abstract: The reduced development of COVID-19 for children compared to adults provides some tantalizing clues on the pathogenesis and transmissibility of this pandemic virus. First, ACE2, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) receptor, is reduced in the respiratory tract in children. Second, coronavirus associated with common colds in children may offer some protection, due to cross-reactive humoral immunity and T cell immunity between common coronaviruses and SARS-CoV-2. Third, T helper 2 imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 53 publications
3
94
0
6
Order By: Relevance
“…144 Frequent recurrent viral infections could also induce an enhanced state of activation of the innate immune system, including epigenetic changes in trained immunity, making it easier to clear SARS-CoV-2. 134 Cross-reactive coronavirus antibodies and T cells Althoughit has been suggested that children might be protected against SARS-CoV-2 as a result of pre-existing cross-reactive antibodies from more frequent and recent HCoVs infections, 145 preliminary data show that, while antibodies to HCoVs crossreact with the spike protein of SARS-CoV-2 and SARS-CoV, these antibodies are rarely neutralising, as they do not bind to SARS-CoV-2 receptor binding domain. [146][147][148][149] In accordance with this, no difference in antibody levels against HCoVs was found between children infected with SARS-CoV-2 and those who were not infected.…”
Section: More Frequent Recurrent and Concurrent Infectionsmentioning
confidence: 99%
“…144 Frequent recurrent viral infections could also induce an enhanced state of activation of the innate immune system, including epigenetic changes in trained immunity, making it easier to clear SARS-CoV-2. 134 Cross-reactive coronavirus antibodies and T cells Althoughit has been suggested that children might be protected against SARS-CoV-2 as a result of pre-existing cross-reactive antibodies from more frequent and recent HCoVs infections, 145 preliminary data show that, while antibodies to HCoVs crossreact with the spike protein of SARS-CoV-2 and SARS-CoV, these antibodies are rarely neutralising, as they do not bind to SARS-CoV-2 receptor binding domain. [146][147][148][149] In accordance with this, no difference in antibody levels against HCoVs was found between children infected with SARS-CoV-2 and those who were not infected.…”
Section: More Frequent Recurrent and Concurrent Infectionsmentioning
confidence: 99%
“…The reasons for milder disease in children are presently unclear. Possible contributing factors include more robust early innate immune responses [ 71 ], cross-protection from seasonal coronavirus exposure, differences in ACE2 expression, nonspecific effects of vaccination and greater memory T-cell diversity [ 72 , 73 ]. The mild course of COVID-19 is quite different from other respiratory illnesses in children, such as influenza and respiratory syncytial virus, which impact children more severely than adults and in which children are the major mediators of transmission.…”
Section: Clinicalmentioning
confidence: 99%
“…Respiratory viruses such as influenza and respiratory syncytial virus (RSV) remain the leading causes of ARI in under five children [1] . The immature immune system have been linked to increased risk of infectious diseases, particularly respiratory viral infections in infants [1] , However, as the research on ongoing pandemic (Corona Virus Disease 2019 (COVID-19)) caused by a novel respiratory virus, Severe Acute respiratory Syndrome- Coronavirus – 2 (SARS-CoV-2) continues to grow, it appears that young children are less susceptible to this SARS-CoV-2 [2] . Current research suggests that the lowered susceptibility in children is likely due to the scarcity of the SARS-CoV-2 angiotensin-converting enzyme 2 (ACE2) receptor in the respiratory tract in children, meaning that the virus has less receptors to bind to and take hold within a child’s respiratory tract [3] .…”
Section: Introductionmentioning
confidence: 99%
“…It is also hypothesised that higher rates of prior infection with other human coronavirus in children may provide protection against severe SARS-CoV-2 infection in children [4] . Additionally, emerging evidence suggest most laboratory confirmed cases of COVID-19 in children results in mild disease, with severe disease in children considered rare [2] . Limited data are available relating to host immunologic response to COVID-19 infection in young children; nevertheless, it is evident that children do get infected with COVID-19 and around 12–18% of infected children are aged < 12 months [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%